Reação do mercado ao ingresso (saída) do índice de sustentabilidade empresarial (ISE): estudo de evento e análise da liquidez - Kruel, Maximiliano (2011)
The present work analyzes investor´s reaction of the entrance and exit companies‟ assets who adhere to Enterprise Sustainability Index (ISE) of the Stock exchange of São Paulo, between years 2005-2009, and search to identify possible alterations in the liquidity ratios for some variables. Through the event study methodology and the influence of market liquidity test, this paper brings evidence of market performance through out semi strong market efficiency. Seven indicators of liquidity had been selected to identify the differences in the ingression (exit) of the Enterprise Sustainability Index: market index return of BOVESPA and FGV 100, financial volume, IBOVESPA weighted volume, turnover and three different spread relative. The results demonstrate that even information have being previously published of the ingression (exit) of ISE index, it does not have returns above of the waited ones, although there are existence of bigger, positive and negative average residues, in some instants, previous and subsequent of the event date. The liquidity tests had been found relations only for complete samples of the companies‟ assets. The ingression (exit) can only be verified relation with the return of the index, BOVESPA and FGV 100. In such a way, it can be inferred that the results are in accordance with the Efficiency of Market (FAMA, 1970). According of the market efficiency theory in the semi strong form, the companies‟ actions of the Enterprise Sustainability Index are already presents in their assets prices.